One-pot synthesis of natural-product inspired spiroindolines with anti-cancer activities. Issue 3 (16th December 2021) - Li, Shi-Qiang; Yan, Wei; He, Liu-Jun; Zhang, Ming; Tang, Dian-Yong; Li, Hong-yu; Chen, Zhong-Zhu; Xu, Zhi-Gang
Abstract : A post-Ugi/diastereoselective cascade reaction was developed to construct the spiroindoline scaffold through a 5- exo-dig indole cyclization and the intramolecular trapping of the spiro intermediate forming a quaternary carbon center. Abstract : A post-Ugi/diastereoselective cascade reaction was developed to construct naturally existing spiroindolines via a facile and metal-free one-pot protocol. During the construction, a new C–C bond was formed through a selective 5- exo-dig indole cyclization on the propiolamide; and a new C–N bond was diastereoselectively formed which controlled the configuration of three chiral centers simultaneously. Screening data of several difficult-to-inhibit cancer cell lines demonstrated that (±)-6d could strongly inhibit colon cell U87 proliferation with an IC50 value of 0.19 ± 0.04 μM. Taken together, our research provided a novel and robust protocol towards the synthesis of spiroindolines and revealed their potential application as anti-cancer agents in diverse human cancer cell lines.